Mobile Android-Based Snack Food Production Management Information System (A Case Studi Of Mirasa Gendhis Sriyanti Tape Candy Factory) - Titi, Niken; Ardiani, Farida (SEAN Institute, 2024)
The snack industry, including the Mirasa Gendis Sriyanti Candy Factory in Magelang, faces various operational issues such as ineffective stock control, overproduction risks, and discrepancies between production processes and market demand. These challenges often lead to excess stock, inefficient costs, and financial losses. As a small business, the factory needs to adopt modern technological solutions to improve operational efficiency, particularly in production and inventory management. This study focuses on developing a mobile-based Production Management Information System called Sweet Candy for the factory. The application utilizes Firebase as its backend for real-time data storage, facilitating efficient management of production, scheduling, inventory, and reporting tasks. The system is built using Android Studio and Kotlin, offering features such as input for production requests, scheduling, and monthly reporting. Black box testing confirmed that the application meets the necessary requirements and performs as expected. This study contributes to the digitalization of small and medium-sized enterprises (SMEs) by presenting an innovative approach to production management.